Quantum Model of Simple Motion and Objects Positions Based on Controlled Operations - Joanna WIŚNIEWSKA; Marek SAWERWAIN (Communications of International Proceedings, 2021)
The article presents an outline of a new project concerning simulation of motion in a quantum register. One part of the register contains identifiers of objects, and the other their locations. Using controlled versions of known operations, like Hadamard gate and Grover’s diffusion operator, we can manage with the moves of pointed out object.
Keywords: Quantum States; Quantum Gates; Unitary Controlled Operations.